Business Cycle Synchronization of a Small Open EU-Candidate Country’s Economy with the EU Economy - Filipovski, Vladimir; Trpeski, Predrag; Bogoev, Jane (Panoeconomicus, 2018)
The objectives of this paper are to empirically identify business cycles in a small open EU-candidate country such as the Republic of Macedonia and to assess the degree of synchronization of the country’s business cycle with the cycle of the EU economy. Towards the first objective, we apply linear and nonlinear methods for delineating the production gap cycle in the Macedonian economy. As for the second objective, we apply autoregressive methods to assess the size and speed of cyclical adjustment of the Macedonian economy to output shocks to the Euro-zone economy. The results of our analysis suggest a high degree of synchronization of the Macedonian business cycles with the cycles of the EU economy. Also, the shocks in economic activity in the Euro-zone economy are transmitted almost instantaneously, and with a large magnitude, to the Macedonian economy. Finally, the impact of the Euro-zone output contraction is less pronounced than the impact of the Euro-zone output expansion, suggesting an impact of the country’s autonomous countercyclical economic policies.Key words: Business cycles, Exogenous shocks, Potential output, Filter methods, Asymmetric adjustment.JEL: E32, F41, F62, C13, C22.Sinhronizacija poslovnog ciklusa ekonomije male otvorene zemlje kandidata za Evropsku uniju sa ekonomijom Evropske unijeCilj rada je da se empirijski identifikuju poslovni ciklusi u maloj otvorenoj zemlji kandidatkinji EU kao što je Republika Makedonija kao i procena stepena sinhronizacije poslovnog ciklusa zemlje sa ciklusom ekonomije EU. Prema prvom cilju, primenjujemo linearne i nelinearne metode za određivanje ciklusa proizvodnog jaza u Makedonskoj ekonomiji. Što se tiče drugog cilja, primjenjujemo autoregresivne metode za procenu veličine i brzine cikličnog prilagođavanja Makedonske ekonomije na šokove proizvodnje u ekonomiji eurozone. Rezultati naše analize ukazuju na visok stepen sinhronizacije Makedonskih poslovnih ciklusa sa ciklusima ekonomije EU. Takođe, šokovi u privrednim aktivnostima u ekonomiji evrozone prenose se skoro trenutačno i u velikoj meri na Makedonsku ekonomiju. Na kraju, uticaj smanjenja proizvodnje u evrozoni je manje izražen nego uticaj ekspanzije proizvodnje u evrozoni, što ukazuje na uticaj autonomnih kontracikličnih ekonomskih politika u zemlji.Ključne reči: Poslovni ciklusi, egzogeni šokovi, potencijalna proizvodnja, metode filtriranja, asimetrično podešavanje.